187 Expert-developed ICD-AIS map for measuring serious road traffic injuries. (1st September 2016) - Barnes, Jo; Price, Jan; Gillich, Patrick; Brammer, Amy; Read-Allsopp, Christine; Nayduch, Donna; Baus, Katherine; Cookman, Kathy; Loftis, Kathryn; Jones, Lauren; Brennan, Maureen; Stanley, Patsye; et al.
Abstract : Background: The problem of serious road injury has not decreased in comparison to the drop in fatal road injuries. Unlike the standard definition adopted for fatal road injuries, serious injury has not been as well defined in Europe. However in 2012 the High Level Group on road safety agreed to the defining of serious injury in EU countries as Maximum Abbreviated Injury Scale 3+ (MAIS3+). The AAAM was commissioned by the Transport and Mobility, Road Safety Unit of the European Commission to develop a MAIS3+ serious injury map from the International Classification of Diseases (ICD-9 and ICD-10) to the Abbreviated Injury Scale (AIS 2005 Update 2008). Methods: The study involved an expert panel comprising ICD coding experts and certified AIS specialists to map ICD-9-CM and ICD-10-CM codes to the AIS 2005 Update 2008 identifying the following levels of severity: MAIS3+ injury, MAIS 1 and 2 and 'no map' cases. Rules were invoked based on the AIS principles of coding practice to ensure the MAIS descriptors were a true reflection of how an injury descriptor in ICD would be coded manually to the AIS by a certified AIS specialist. Results: Overall for the injury-based codes of ICD-9-CM, 781 codes (31%) were mapped to a MAIS severity at the level of MAIS3+, 1297 codes (52%) were mapped at the level of MAIS1 or 2 and 426 codes (17%) could not be mapped. For the much larger set of injury-based codes of ICD-10-CM, 2323 codes (14%) were mapped to a MAIS severity at the level of MAIS3+, 9700 codes (59%) at the level of MAIS1 or 2, and 4485 (27%) could not be mapped. Conclusions: The application of the AAAM's expert derived AIS-ICD map is a solid foundation for identifying serious injury at MAIS3+ for road traffic injuries. This AIS-ICD map offers a comprehensive approach to serious road injury definition for the EU and will enable countries to set measureable road safety targets for the reduction of serious road traffic injury using a comparable definition.